Fetal repercussions of Zika virus infection during pregnancy - Almeida,Catarina Lopes de (2017)
Recently, Zika virus infection has been rapidly spreading, rising the cases of fetal abnormalities. A review was performed from February 2016 to January 2017, selecting articles that evaluated the fetal repercussions of maternal infection, considering fetal autopsies, clinical examinations and imagiology. The most frequent abnormalities were in the central nervous system, namely microcephaly, intracranial calcifications and ventriculomegaly. Death and fetal growth restriction were also reported. Anomalies in other systems were found to a lesser extent. Despite enough evidence proving this causality, it is important to document all these changes, allowing the comprehension of the virus' full width